Stone Memories, Sculptured History: Multiple Readings of Manitoba’s Legislative Building - Fulford, George; Leverick, Jane; Wilde, Kimberley; Fowler, Maria; Unrau, Kara Peters; Hill, Arden; Wakshinski, Barbara (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
This paper incorporates the concept of “positioning” into a semiotic analysis of the architectural and decorative features of the Manitoba legislature. The authors interpret features of the legislature in the context of hegemonic assertions about governance and authority that were prevalent at the time the legislature was built. Using concepts developed by Yates, Langer, Schapiro, Barthes, Lévi-Strauss, Derrida and Foucault, the authors challenge these assertions from their own context as positioned subjects in a pluralistic, postcolonial and postmodern world.